Elevated Temperature Oxidation and Corrosion of a Titanium Aluminide Alloy - Leggett, Jonathan (Cranfield University, 1997)
Titanium aluminides are being developed to expand the temperature capability of titanium alloys with maximum service temperatures around 700*C. These materials also have the ability to replace nickel superalloys with potential applications in the high pressure compressor, and in the 4th stages of the low pressure turbine. The above applications place these alloys in environments not previously considered. Within the compressor hot salt corrosion may be a problem with salt ingested from the atmospheric aerosol. While in the turbine the combination of salt ingestion,and SO, from the burning of fossil fuels, results in hot corrosion being a potential problem. In this study the individual effects of salt and So2 were investigated, with corrosion mechanisms being proposed using kinetic, metallographic and thermodynamic data. Understanding these effects enabled both the hot salt corrosion and hot corrosion behaviour of TiAl alloys to be evaluated. In air alone continuous alumina layers, within a mixed alumina/rutile scale, provide the oxidation resistance of TiAlNb alloys. Logarithmic kinetics operated for 100 hours at 700*C and for 13 hours at 750'C. Parabolic kinetics then operated out to 100 hours at 900*C. Mass gains ranged from 0.06 to 2.1mg/cO after 100 hours at 700 and 900'C respectively. This situation changes in bi-oxidant, air/S02, atmospheres where increased growth rates are linked to the formation of a continuous sulphide layer at the scale/substratien terface. Below 800'C logarithmic/parabolic kinetics operate. At and above 800*C initial logarithmic kinetics change to near linear/breakaway kinetics with spallation becoming a problem. Mass gains,after 100 hours, ranged from 0.2 mg/cM2 at 700"C up to 6.4 mg/cm2 at 900"C. The presence of low salt concentrations [<0.05mg/cm2] resulted in severe substrate degradation, with preferential attack down a2 lathes.The first 10-20 hours were shown to be the most important with low melting point salt mixtures spreading across the surface, increasing the rate of attack. The evolution of HCI/Cl2 during initial substrate attack leads to the Vapour Phase Transport of aluminium and manganes chlorides resulting in whisker growth over a porous rutile scale. The presence of salt modified the diffusion controlled kinetics under purely oxidising conditions. Chlorine was shown to promote the vapour phase transport mechanism which resulted in the initial accelerated logarithmic kinetics. A change to parabolic type kinetics occurred due to the loss of chlorine to the atmosphere. The mass gains, after 100 hours, ranged from 0.06 to 1.1rn g/cm2 between 500 and 800* C. The combination of salt deposits and S02 bearing environments resulted in severe substrate degradation. Salt played a dominant role during the early stages of corrosion, whilst low partial pressuresof S02 affected the later stages of corrosion. Non protective oxide scales were developed with low melting point MnSO4-Na2SO4 mixtures forming at salt deposits and a continuous sulphide layer at the scale/substrate interface. R apid scale growth resulted in severe scale spallation. The initial stages of hot corrosion followed rapid logarithmic type kinetics. Further increases in the corrosion rate where promoted by the formation of continuous sulphide layers at the scale/substrate interface.Parabolic kinetics, at this stage, were followed by linear growth rates once scale spalling occurred. Mass gains, after 100 hours, ranged from 0.52 to 3.89 mg/cm2between 650 and 800"C.